Analisis Hubungan Kesadaran Keamanan, Privasi Informasi, dan Perilaku Keamanan Pada Para Pengguna Media Sosial Line - Irfan Arif Afandi; Ari Kusyanti; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
LINE is the messaging application that often used as a way to non-normative act and used as media is looking for profit or benefit unilaterally by the peoples who work in cyber crime. This research attempted to explore the main factors affecting security behavior of LINE users. The research model comprised of eight constructs. The constructs were security awareness, self-effiacy in information security, expectation, security behavior, cues to action, perceived susceptibility/perceived severity, perceived security threat, and internet users information privacy concerns. It analyzed data collected from qustionnaire survey on users of LINE. Correlations and strength of corelations between laten constructs were identified using Structural Equation Modeling (SEM). The result of this research show that Cues to Action have significant and positive influence on Perceived Security Threat; Self-Efficacy in Information Security have significant and positive influence on Expectations; Perceived Security Threat have significant and positive influence on Internet Users Information Privacy Concerns; and Perceived Security Threat have significant and positive influence on Security Behavior.